1992
DOI: 10.1111/j.1600-0722.1992.tb01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength of porcelain on cast vs. wrought titanium

Abstract: The bond strength of porcelain fused to cast and wrought titanium surfaces was calculated from fracture loads in a 4‐point bending test. Two different porcelain were applied (O'Hara and Duceratin). The surface of Ti‐cast specimens was treated in two different ways to produce variations in the impurity level before porcelain veneering. Microhardness measurements as well as scanning electron microscopy with EDX analysis were conducted. The results showed no significant difference in bond strength between the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
3
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 4 publications
2
41
3
3
Order By: Relevance
“…For all materials tested (except for cp Ti), the selection of 250 µm grit size and up to 0.30 MPa application pressure provided the lowest retention of alumina fragments, in agreement with results of previous studies in which fragment retention decreased with increasing grit size 11,14,16,24) . Previous studies have reported significantly higher metal-ceramic bond strengths 13,25) for surfaces sandblasted with 250 µm-grit alumina particles, a finding that might be explained by decreased alumina fragment retention under these conditions. Some manufacturers suggest that a 45° incidence angle of airborne particles facilitates their deflection from the surface, an assertion supported by some limited evidence 20) , but not yet fully documented.…”
Section: Groupsmentioning
confidence: 97%
See 1 more Smart Citation
“…For all materials tested (except for cp Ti), the selection of 250 µm grit size and up to 0.30 MPa application pressure provided the lowest retention of alumina fragments, in agreement with results of previous studies in which fragment retention decreased with increasing grit size 11,14,16,24) . Previous studies have reported significantly higher metal-ceramic bond strengths 13,25) for surfaces sandblasted with 250 µm-grit alumina particles, a finding that might be explained by decreased alumina fragment retention under these conditions. Some manufacturers suggest that a 45° incidence angle of airborne particles facilitates their deflection from the surface, an assertion supported by some limited evidence 20) , but not yet fully documented.…”
Section: Groupsmentioning
confidence: 97%
“…The presence of such embedded fragments adversely affects the bond strength of metal-ceramic 8,11) and metal-resin 12) systems, decreasing the mechanical interlocking and inhibiting the chemical bonding of porcelain with metallic oxides [13][14][15] . In implant technology, sandblasting with alumina grains is also used for surface roughening in combination with acid-etching to enhance osseointegration 16) , but concerns have been raised regarding the impact of alumina fragments embedded in these surfaces on their eventual osseointegration 17) .…”
Section: Introductionmentioning
confidence: 99%
“…Sandblasting with alumina (Al2O3) is one of the methods that are recommended for creating surface irregularities and providing mechanical interlocking force for porcelain. Derand et al 16) and Lautenschlager et al 17) found significant amounts of alumina particles embedded in the titanium-porcelain interface, which is attributed to the sandblasting surface treatment. The presence of such particulates may have an adverse effect on weakening the mechanical interlocking of porcelain to metal by introducing stress concentration points 16,17) .…”
Section: Introductionmentioning
confidence: 99%
“…Derand et al 16) and Lautenschlager et al 17) found significant amounts of alumina particles embedded in the titanium-porcelain interface, which is attributed to the sandblasting surface treatment. The presence of such particulates may have an adverse effect on weakening the mechanical interlocking of porcelain to metal by introducing stress concentration points 16,17) . Improving the bond strength of porcelain to titanium is important for enhancing its clinical usability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation